The networking behavior of Indian executives under environmental uncertainty abroad: An exploratory analysis - Srivastava, Mohit; Moser, Roger; Hartmann, Evi (Journal of Business Research, 2018)
Focused networking has become a significant source of effective internationalization. Prior research has shown that networking can improve the internationalization performance of companies, as local contacts provide access to relevant information that is typically unavailable otherwise. Several factors, such as the level of environmental uncertainty faced abroad, can significantly affect the optimal networking of senior executives in foreign markets. However, there is a lack of research about how environmental uncertainty affects ideal networking behavior. In this study, we examined the impact of the fit between environmental uncertainty and the networking behavior of Indian executives on the internationalization performance of their companies. We collected data from 197 Indian executives with significant experience in European and other markets to test our model. We examined five potential environmental uncertainty factors, including the FDI-related environment, the macroeconomic environment, the material and infrastructure environment, the consumption environment and the competitive environment, as well as four networking behavior dimensions, including proactivity, commitment, strategy and tie strength. The results from a profile deviation analysis reveal that ideal networking behavior profiles exist for different types and levels of environmental uncertainty. In summary, the findings from the study provide useful guidelines for Indian and other executives about how to network abroad given different types and levels of environmental uncertainty, and they offer new perspectives to improve the internationalization performance of these executives.
Keywords: Internationalization; Environmental uncertainty; Networking; Profile deviation; Ideal profiles